Hubungan Pengetahuan, Sikap, Dan Tindakan Orang Tua Tentang Pemberian Stimulasi Motorik Kasar Terhadap Kemampuan Berjalan Anak - AWANIS, Almas, Agus Widodo, S.Fis, M.Kes, Isnaini Herawati, SSt. FT, M. Sc (2015)
Background: Stimulation of gross motor skills such as walking becomes important given by the parents because it will affect the child's social behavior (social interaction) in the future. Stimulation is given as a form of parenting behavior, and influenced by knowledge, attitude, action about gross motor stimulation. The Purpose of Research: To find out the relationship of knowledge, attitudes and actions of parents about gross motor stimulation to the ability walk of children. The Benefit of Research: It could know about relationship of knowledge, attitudes and actions of parents about gross motor stimulation to the ability walk of children. The Method of Research: This research is an observational study with cross sectional design. The method taking of the sample is total population, so the sample is all parents (father, mother or grandmother) who have children are in a phase of walking or passed of walk phase with 2 years the maximum age and selected based with criterian insklusion and eksklusion. Techniques of statistical tests using Chi-Square with degree of confident of 95%. Result of the Research: The results showed that there is a no relationship of knowledge of parents about gross motor stimulation to the ability walk of children (p= 0.865), no relationship of attitudes of parents about gross motor stimulation to the ability walk of children (p=0.747), and no relationship of actions of parents about gross motor stimulation to the ability walk of children (p=0.106). Conclution: Statistically concluded that there is a no relationship of knowledge, attitudes and actions of parents about gross motor stimulation to the ability walk of children.